Model Pembelajaran Tematik Terpadu Berbasis Teks Bermuatan Pendidikan Literasi Humanis - Simpun Simpun; Dina Mardiana; Sapriline Sapriline (FKIP, Universitas Palangka Raya, 2023)
The 21st century learning involving artificial intelligence indeed cannot replace one's humanist character. This is the importance of an educator in the primary school (SD) having a humanist educator soul to create a superior generation by realizing Pancasila character. Students in the Primary School Teacher Education (PGSD) Study Program as teacher candidates should be able to prepare their competencies in designing text-based integrated learning with humanist literacy education. This is done in order to build a humanist character based on Pancasila values to the students. The research was conducted to design an integrated learning of lecturing model that implements a text-based approach filled with humanist literacy education. This integrated learning of lecturing model was used to build Pancasila Student Profile for designing integrated learning tools in the PGSD Study Program of the University of Palangka Raya. The implementation of this research used a qualitative-quantitative method (mixed-method research design). The qualitative method is used to design the lecturing model and the quantitative method is used to test the effectiveness of the lecturing model using the Wilcoxon Test. The results show the average score of pre-test was 56 and that of post-test was 78. Furthermore, the results of the pre-test-post-test were analyzed for their level of effectiveness using the Wilcoxon test which showed p=0.000 where p<0.05 meaning Ho was rejected. Hence, the use of lecturing model by orienting the Integrated Learning Theory and Practice using a text-based approach with humanist literacy education is effectively used in increasing student learning outcomes (CPL). This result brought a positive outcome to students through the course taught to design integrated thematic learning device using the text-based approach containing humanist literacy education to build the Pancasila Student Profile.